Analisa Investasi Alat Berat Dalam Jangka Waktu 5 Tahun Produktif Di Papua Tengah Kab Mimika - Toding, Rahel; Abduh, M. Natsir; Mulyani, Savitri Prasandi (Jurnal Penelitian Teknik Sipil Konsolidasi, 2026)
Mimika Regency, Central Papua is currently facing geographical challenges. Timika's location far from the national distribution center causes limited access to goods and services, including heavy equipment. This condition is exacerbated by high logistics costs, minimal local providers, and underdeveloped transportation infrastructure. One case occurred in the Wandai Jaya company project, which experienced delays due to the unavailability of motor graders for rental. The delay had an impact on the postponement of the work resulting in disruption of the project schedule and the potential for financial losses and the company's reputation. Therefore, a long-term heavy equipment procurement strategy is needed. This study analyzes the feasibility of procuring motor graders through three methods, namely cash purchases, credit purchases, and rentals, using the Benefit Cost Ratio (BCR) approach. The calculation results show that the credit method produces a total cost of IDR 1,838,213,558 with a BCR of 0.01, cash purchases of IDR 1,450,000,000 with a BCR of 0.14, and rentals of IDR 2,925,000,000 with a BCR of 2.4. Based on the analysis, the rental method proved to be the most economically profitable. This finding can be the basis for decision making in heavy equipment procurement to improve project efficiency, especially in areas with logistical challenges such as Timika.